Pengelolaan sampah dengan pendekatan Asset-Based Community Development (ABCD) di wilayah pesisir Bulukumba Sulawesi Selatan - Fatmawaty Mallapiang; Yessy Kurniati; Sukfitrianty Syahrir; Abd. Majid HR Lagu; Rimawati Aulia Insani Sadarang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Waste becomes a crucial problem in coastal areas because of the habit of people who throw garbage directly into the sea. This community service aims to manage waste by empowering assets owned by the community. This activity is carried out in 2 stages, namely the preparation and implementation stages. The preparation phase is carried out by inventorying assets owned by the community, conducting socialization, preparing materials and materials needed for waste management training. The identified assets owned by the community consist of physical assets, human assets, social assets, financial assets, and natural assets. The results of the activity showed that the participants who were present did not reach the target due to the sea fishing activities carried out by residents. Participants who took part in the waste management activities were quite enthusiastic in participating in the material and simulation. It is expected that participants who follow the training can process their garbage and motivate other residents to handle their waste.